Evaluation of monocyte to high-density lipoprotein cholesterol ratio in the manic state of bipolar disorder - Yusuf Çokünlü; Ali Metehan Çalışkan (SERNEV, 2021)
Introduction: Bipolar disorder has been linked to abnormalities in the immune/inflammatory functions. Monocyte to high-density lipoprotein (HDL) cholesterol ratio (MHR) is used as chronic inflammation markers. The aim of this retrospective study was to investigate the MHR levels in manic patients with bipolar disorder.Methods: The study included 100 male patients, 49 of whom were in the first episode and 51 of whom had multiple episodes, hospitalized with a diagnosis of bipolar disorder manic state and 50 healthy individuals with characteristics comparable to the patient group in terms of gender and age. MHR values were calculated on the basis of the obtained hemograms, and the results of the biochemistry blood tests and lipid panel analyses and recorded. Kruskal Wallis test was used to compare the MHR values among the first episode, multiple episodes, and healthy control groups.Results: There was no statistically significant difference between the patients and controls in terms of age, whereas the mean age of the patients who had multiple episodes was significantly higher than the first episode. MHR values were found to be statistically significantly higher in the first episode and multiple episodes group than healthy controls. There was no statistically significant difference between the MHR levels of the patients, who were in the first episode, and of the patients who had multiple episodes.Conclusion: This study is consistent with the results of studies reporting inflammation in the manic episode of bipolar disorder and therefore may indicate the presence of inflammation in the manic episode.